2002
DOI: 10.1074/jbc.m205478200
|View full text |Cite
|
Sign up to set email alerts
|

Protein-tyrosine Phosphatase-ς Is a Novel Member of the Functional Family of α-Latrotoxin Receptors

Abstract: Receptor-like protein-tyrosine phosphatase sigma (PTP ) is essential for neuronal development and function. Here we report that PTP is a target of ␣-latrotoxin, a strong stimulator of neuronal exocytosis. ␣-Latrotoxin binds to the cell adhesion-like extracellular region of PTP . This binding results in the stimulation of exocytosis. The toxin-binding site is located in the C-terminal part of the PTP ectodomain and includes two fibronectin type III repeats. The intracellular catalytic domains of PTP are not req… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
48
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(48 citation statements)
references
References 46 publications
0
48
0
Order By: Relevance
“…Its exocytotic effect requires binding to neuronal receptors (Grasso et al, 1980). Three classes of receptors have been identified: (1) neurexin 1␣, a neuronal protein with a single transmembrane domain (Ushkaryov et al, 1992), (2) CIRL/latrophilin 1 (CL1) (Davletov et al, 1996;Krasnoperov et al, 1997), a member of the CL family, which are G-protein-coupled receptors Ichtchenko et al, 1999), and (3) protein tyrosine phosphatase (Krasnoperov et al, 2002a), a recently found receptor for the toxin. In either neurexin 1␣ or CL1 knock-out mice (Geppert et al, 1998;Tobaben et al, 2002), the neuronal sensitivity to ␣-latrotoxin was reduced, indicating that these two receptors constitute the major receptors for ␣-latrotoxin.…”
Section: Introductionmentioning
confidence: 99%
“…Its exocytotic effect requires binding to neuronal receptors (Grasso et al, 1980). Three classes of receptors have been identified: (1) neurexin 1␣, a neuronal protein with a single transmembrane domain (Ushkaryov et al, 1992), (2) CIRL/latrophilin 1 (CL1) (Davletov et al, 1996;Krasnoperov et al, 1997), a member of the CL family, which are G-protein-coupled receptors Ichtchenko et al, 1999), and (3) protein tyrosine phosphatase (Krasnoperov et al, 2002a), a recently found receptor for the toxin. In either neurexin 1␣ or CL1 knock-out mice (Geppert et al, 1998;Tobaben et al, 2002), the neuronal sensitivity to ␣-latrotoxin was reduced, indicating that these two receptors constitute the major receptors for ␣-latrotoxin.…”
Section: Introductionmentioning
confidence: 99%
“…The general picture concerning the influence of ectodomain ligands over RPTP function has therefore yet to be formed. PTP can bind to at least three extracellular ligands (5,27,45). Although the role of ligand interactions is currently unclear, it is likely that they influence the biological functions of this phosphatase (6,15,33,42,44,46,49,56,60).…”
mentioning
confidence: 99%
“…PTP is a large, highly conserved cell adhesion molecule-like RPTP that binds several unrelated extracellular ligands (5,27,45). PTP functions in the nervous system to control axon development and regeneration (42,44,46,49,56), the maturation and myelination of nerves (15,33,60), and the development of the hypothalamopituitary axis (6,15,60).…”
mentioning
confidence: 99%
“…This property has been extensively exploited to investigate the molecular mechanisms underlying exocytosis (1,2). Toxin action requires first the binding to a surface receptor, and three distinct receptors for ␣-LTX have been identified: the latrophilins (LPHs), which contain a large extracellular adhesion molecule domain and a C-terminal portion bearing the signature of G-protein-coupled receptors (3,4), neurexin Ia and ␤ (2), and the receptor-like protein-tyrosine phosphatase (5). It is generally accepted that the toxin inserts subsequently as a tetramer into membranes to form a stable, cation-permeable pore (6), and the ensuing Ca 2ϩ influx plays a major role in the activation of exocytosis.…”
mentioning
confidence: 99%